2020
DOI: 10.1080/09638237.2020.1793124
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision-making preferences in mental health: does age matter? A systematic review

Abstract: Background: Research to date suggests older adults prefer a passive involvement in the clinical decision-making process; however, the empirical evidence underlying this claim in the mental health context is yet to be reviewed systematically.Aims: To understand whether older adults desire involvement in mental health-related clinical decisions.Method: A systematic review was conducted to identify primary research that explored mental-health decision-making preferences of people with a mean age of over 55 from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Previous investigation shows that most patients with mental disorders want to participate in the decisions about their treatment [ 45 47 ]. However, patient participation in research and development of PtDAs is almost absent in GAD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigation shows that most patients with mental disorders want to participate in the decisions about their treatment [ 45 47 ]. However, patient participation in research and development of PtDAs is almost absent in GAD.…”
Section: Discussionmentioning
confidence: 99%
“…Although extant research on information preferences is limited, findings indicate that adults with mental health problems and their families have many information needs that remain unaddressed (Buckland, 1994; Cleary et al ., 2005; Drapalski et al ., 2008; Fossey et al ., 2012; Burns et al ., 2021). The unmet information needs of older adults include information about mental health problems, outcomes of mental health problems, treatment options and individual treatment progress (Fossey et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Inpatient and outpatient young- to middle-aged adults with mental health problems, as well as their care-givers, desire enhanced information, preferring knowledge on: steps to take if feeling unwell; information about medication treatment; knowledge about the ways in which others cope with similar mental health problems; and information about mental health services in the community (Cleary et al ., 2005). A recent systematic review exploring shared decision-making preferences in mental health highlighted older adults’ desire for involvement in mental health-related treatment decisions (Burns et al ., 2021). Conclusions prompted a call for more ‘high-quality research regarding the shared decision-making preferences and outcomes of older adults with mental ill-health’ (Burns et al ., 2021: 634).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions based on SDM, such as Patient Decision Aids (PtDAs), have shown to improve patients’ knowledge about available treatments and its benefits/risks, decisional conflict, concordance between patients’ preferences and choices, satisfaction and other variables related to the decisional process [ 11 ]. Different studies have observed that mental health patients, including those with AD, are willing to participate and become involved in the decisions about their care, a desire that is often not satisfied [ 12 , 13 , 14 ]. Unfortunately, the number of interventions designed to promote SDM in the field of mental health disorders, and specifically GAD, are still scarce [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%